The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1074/jbc.m606656200
|View full text |Cite
|
Sign up to set email alerts
|

Negative Regulation of Osteoclastogenesis by Ectodomain Shedding of Receptor Activator of NF-κB Ligand

Abstract: Receptor activator of NF-B ligand (RANKL) is a transmembrane glycoprotein that has an essential role in the development of osteoclasts. The extracellular portion of RANKL is cleaved proteolytically to produce soluble RANKL, but definite RANKL sheddase(s) and the physiologic function of RANKL shedding have not yet been determined. In the present study, we found that matrix metalloproteinase (MMP) 14 and a disintegrin and metalloproteinase (ADAM) 10 have strong RANKL shedding activity. In Western blot analysis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
162
1
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(189 citation statements)
references
References 40 publications
8
162
1
7
Order By: Relevance
“…RANKL is produced as a 45 kDa membrane-associated protein, as a 31 kDa soluble protein by proteolytic cleavage, or as a 39.5 kDa soluble protein following expression of the hRANKL3 isoform [24]. In murine models, the membrane form is more active than the soluble ones [24][25][26]. sRANKL is present in blood circulation both in the free form and as a complex with OPG, but the sensitivity of available assays is still insufficient to detect the free form of sRANKL in a significant proportion of healthy individuals [3,4].…”
Section: Discussionmentioning
confidence: 99%
“…RANKL is produced as a 45 kDa membrane-associated protein, as a 31 kDa soluble protein by proteolytic cleavage, or as a 39.5 kDa soluble protein following expression of the hRANKL3 isoform [24]. In murine models, the membrane form is more active than the soluble ones [24][25][26]. sRANKL is present in blood circulation both in the free form and as a complex with OPG, but the sensitivity of available assays is still insufficient to detect the free form of sRANKL in a significant proportion of healthy individuals [3,4].…”
Section: Discussionmentioning
confidence: 99%
“…metalloproteinases, matrix metalloproteinase 14 (MMP14) and a disintegrin and metalloproteinase domain-containing protein 10 (ADAM10), which we identified from enriched EV fraction in response to LPS transfection (Table I). MMP14 and ADAM10 are known to convert transmembrane molecules into a soluble form through a proteolytic process called ectodomain shedding, and they also share common substrates (35,36). In addition, it has also been shown that a close relative and functionally similar protease to ADAM10, ADAM17 (37), can induce proteolytic processing and shedding of macrophage colony-stimulating factor (M-CSF) (38).…”
Section: Intracellular Lps Stimulation Activates Strong Vesicle-mediamentioning
confidence: 99%
“…7,11,12 RANKL is expressed as a transmembrane protein in osteoblasts, whereas OPG is a protein secreted by the osteoblasts acting as a decoy receptor blocking the RANKL-RANK ligand interaction, thus antagonizing the formation of mature osteoclasts. 7,13,14 Our null hypothesis is that there is no difference between the root volumes resulting from the effect of different LFMVs. We sought to study the effects of different LFMVs on orthodontically induced RR and to understand the underlying cellular mechanism of LFMV.…”
Section: Introductionmentioning
confidence: 98%